Ga-substituted Mg-Cd ceramic composites for improving the miniaturization and wideband characteristics of high-frequency antennas. Issue 10 (July 2020) - Gan, Gongwen; Zhang, Dainan; Li, Jie; Wang, Gang; Huang, Xin; Rao, Yiheng; Yang, Yan; Wang, Xueying; Zhang, Huaiwu; Chen, Ray T.
Abstract: Mg0·8 Cd0·2 Fe1.9 Ga0.1 O4 ceramic ferrites were synthesized using a solid-state reaction method at 900, 915, 930 and 945 °C. Crystallization analysis indicated that the change in temperature resulted in obvious changes in the microstructure. SEM images indicated that the grain size increased from 0.8 to 1.8  μ m. Elevated saturation magnetization ( M s ≈ 26 emu/g) and reduced coercivity ( H c ≈ 53 Oe) indicated the excellent soft-magnetic behavior of the ceramics. The real part of the permeability correspondingly increased (29–51), and the real part of permittivity showed a slight fluctuation (20–25) with an increase in the temperature. Consequently, an upward bandwidth ratio ( BWR  ≈ 0.2, 915 °C) and matching characteristic impedance were obtained over a wide frequency range of 1–100 MHz. Additionally, with the low magnetic (tan δ μ ~10 −2 ) and dielectric (tan δ ε  ~ 10 −4 -10 −3 ) tangent values, the proposed materials can act as potential agents for enhancing the bandwidth and miniaturization of antennas operating at high frequencies.